Discusiones en torno de la reforma de la Constitución Federal de 1824 durante el primer gobierno de Anastasio Bustamante (1830-1832) - Andrews, Catherine (El Colegio de México, A.C., 2006)
This article analyses the 1830 public debate, held in the newspapers of Mexico City, over the possibility of reforming the 1824 Federal Constitution. It examines the different projects and plans for constitutional change presented by various state legislatures and by the editorials of the capital's principal newspapers. The paper suggests that many of the important constitutional innovations later established by the 1836 Constitution, such as the introduction of a restricted suffrage and the creation of a fourth governing power, were already being discussed in 1830. It also maintains that these reforms follow liberal constitutional philosophy. As a result, it concludes that the ideologies of the Bustamante government, and, for the same reasons, the architects of the 1836 Constitution, cannot be considered conservatives in the way that Mexican historiography has traditionally portrayed them.